Pharmacokinetic Assessment of Continuous Infusion Ceftolozane/Tazobactam for Drug-Resistant Pseudomonas aeruginosa Left Ventricular Assist Device Driveline Infection. (4th October 2017) - Foster, Rachel; Gould, Alyssa P; Justo, Julie Ann; Okoye, Stella; Nicolau, David P; Bookstaver, P Brandon
Abstract: Background: Pseudomonas aeruginosa is a common pathogen in left ventricular assist device (LVAD) infections. Ceftolozane/tazobactam (C/T) is a β-lactam/β-lactamase inhibitor with activity against P . A eruginosa, including multi-drug-resistant (MDR) isolates. We describe the novel use of continuous infusion (CI) C/T with therapeutic drug monitoring in a 70-year-old man who developed a MDR P . A eruginosa LVAD driveline infection. Methods: The patient received CI C/T 6g IV over 24 hours to facilitate long-term outpatient therapy after receipt of five days of intermittent infusion (3g IV every 8 hours over 1 hour). Blood samples were collected in heparinized tubes immediately prior to and at 6, 12, 18, 24, and 48 hours after initiating CI. The samples were centrifuged at 2, 500 rpm for 10 minute and stored at -80°C until assayed. Ceftolozane and tazobactam concentrations were quantified using previously validated high-performance liquid chromatography (HPLC) methods. Results: Ceftolozane and tazobactam concentrations are shown in Table 1. The susceptibility profile (VITEK® 2) demonstrated the following minimum inhibitory concentrations (MICs): gentamicin ≤ 1 mcg/mL, cefepime = 32 mcg/mL, ciprofloxacin ≥ 4 mcg/mL, meropenem = 8 mcg/mL. Colistin, polymyxin B, and C/T MICs were confirmed via E-test (2 mcg/mL, 2 mcg/mL, and 1.5 mcg/mL, respectively). The patient clinically improved with resolution of signs and symptoms of infection after 6 weeks with CI C/T. Suppressive therapy was continued indefinitely in lieu of source control. A subjective increase in gout pain was reported, but no other major adverse events were noted during therapy. Conclusion: Adequate systemic drug concentrations of C/T well above the MIC were achieved when administered as a CI of 6g over 24 hours. Based on serum ceftolozane concentrations, dose modification of CI may be possible with future evaluation. Continuous infusion represents a potentially well-tolerated delivery for C/T and warrants further study. Disclosures: D. P. Nicolau, Merck: Investigator and Speaker's Bureau, Research support. P. B. Bookstaver, Rock Pointe: Content Developer, Consulting fee